Comparative genome analysis of Psychrobacillus strain PB01, isolated from an iceberg - Choi, Jun Young; Kim, Sun Chang; Lee, Pyung Cheon (Journal of Microbiology and Biotechnology, 2020)
A novel psychrotolerant Psychrobacillus strain PB01, isolated from an Antarctic iceberg, was comparatively analyzed with five related strains. The complete genome of strain PB01 consists of a single circular chromosome (4.3 Mb) and a plasmid (19 Kb). As potential low-temperature adaptation strategies, strain PB01 has four genes encoding cold-shock proteins, two genes encoding DEAD-box RNA helicases, and eight genes encoding transporters for glycine betaine, which can serve as a cryoprotectant, on the genome. The pan-genome structure of the six Psychrobacillus strains suggests that strain PB01 might have evolved to adapt to extreme environments by changing its genome content to gain higher capacity for DNA repair, translation, and membrane transport. Notably, strain PB01 possesses a complete TCA cycle consisting of eight enzymes as well as three additional Helicobacter pylori-type enzymes: ferredoxin-dependent 2-oxoglutarate synthase, succinyl-CoA/acetoacetyl-CoA transferase, and malate/quinone oxidoreductase. The co-existence of the genes for TCA cycle enzymes has also been identified in the other five Psychrobacillus strains.
Keywords: Bacillaceae; Citric Acid Cycle; Energy Metabolism; Environmental Microbiology; Genome, Bacterial; Genomics; Glyoxylates; Ice Cover; Metabolic Networks and Pathways; Plasmids; Iceberg; Plasmid; Psychrobacillus; TCA cycle